Good Governance as Key Driver for Sustainable Development, Peace and Security in Nigeria - Mustapha, Bukar Alhaji; Abdullahi , Hindatu; Sheriff, Umar (Kashere Journal of Politics and International Relations, 2025)
This paper focuses on good governance as the driving force for sustainable development, peace and security in Nigeria. The paper examines good governance as a precondition for rapid economic transformation, peace, security and sustainable development. It also discusses that peace and security are considered all over the world as an avenue for sustainable national development. There can hardly be a consequential sustainable national development without peace and security in any nation. Since Nigeria return to a stable democracy in 1999, there has been an absence of elements of good governance in all facets of governance due to avalanche of decadence bedeviling our nation. Over the years, Nigeria had been experiencing accentuated socio-economic problems of income inequality, shelter, inadequate food, education, health and other necessities of life and other negative factors that impede sustainable development such as abject poverty, corruption, armed robbery, kidnapping, youth unemployment, social-inequality, electoral violence and farmers-headmen conflict. All these crises attributed to lack of good governance. The paper revealed that corruption, lack of party ideology and quota system are among the hindrances to good governance in Nigeria. The paper employed prebendalism as its theoretical framework. It adopts qualitative method of data collection as its methodology. The paper recommends among others that democratic administrators should manifest the spirit of accountability, responsibility and responsiveness to ensure good governance in Nigeria. It concludes that good governance is a sine qua non of development; hence it is a catalyst for sustainable development.